2021
DOI: 10.1042/bsr20203404
|View full text |Cite
|
Sign up to set email alerts
|

Development of next-generation antimicrobial hydrogel dressing to combat burn wound infection

Abstract: Infection of burn wounds often leads to poor healing, sepsis, disability, or even death. Traditional care focuses on early debridement, fluid resuscitation, and intravenous antibiotics but these are often inadequate due to compromised vasculature limiting systemic antibiotics effectiveness. Biofilms in burn wounds are barriers to treatment and are associated with the transition of wounds from acute to chronic non-healing state. Current topical treatments for burn wounds include skin substitutes impregnated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 15 publications
0
18
0
2
Order By: Relevance
“…The antibacterial activity of some biopolymers, such as chitosan, can act synergistically with AMPs ( 33 ). Thus, advanced hydrogel dressings that deliver AMPs are promising against drug-resistant infections in chronic wounds ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…The antibacterial activity of some biopolymers, such as chitosan, can act synergistically with AMPs ( 33 ). Thus, advanced hydrogel dressings that deliver AMPs are promising against drug-resistant infections in chronic wounds ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a number of treatment modalities including both cellular therapies and biofunctionalized materials have gained momentum in regenerative medicine; however, treatment outcomes have been variable and often unsatisfactory as wound infection is still a critical challenge [ 61 ]. It is becoming increasingly clear that healing and regeneration of chronic wounds requires powerful and robust antimicrobial agents to clear infection and provide protection against recurrent infections through sustained and prolonged antimicrobial activity [ 62 ]. Here we have shown that our AgNP hydrogel not only clears infections by eradicating wound biofilms but also significantly improves the regenerative process through its multifunctional properties.…”
Section: Resultsmentioning
confidence: 99%
“…When it comes to the material to be 3D printed, of the types of wound dressing materials present in the market, hydrogel wound dressings are an appropriate choice, owing to their ability to debride, moisturize the wound, [13] and also to absorb exudates. [14] It is also well-established that due to the non-Newtonian behavior of hydrogels, hydrogels are printable as they can be extruded through nozzles or needles with ease and subsequently regain all or part of their viscosities once deposited on the print bed.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Currently, commercially available dressings do not yet have the ability to simultaneously combat infection and provide other beneficial functions such as pain relief and wound healing promotion. [13] As such, the personalization of wound dressings in the treatment of burns to meet…”
mentioning
confidence: 99%